Meningkatkan Kemampuan Siswa dalam Membaca Teks dengan Menggunakan Metode Reading Aloud di Kelas III SDN. No. 028/XI Tanjung Tahun 2017/2018 - Hardianto Hardianto (Universitas Batanghari Jambi, 2019)
This study aims to improve the ability of students to read texts by using aloud reading methods in class III SDN. No. 028 / XI Tanjung in 2017/2018. The research conducted was classroom action research conducted at SDN. No. 028/XI Tanjung. This research was conducted from July to November 2017. The study involved 15 third grade students. Classroom action research was conducted in two cycles (Cycle I and Cycle II) and each cycle consisted of two meetings with four activities namely planning, implementation, observation, and reflection. Data was collected by test and observation techniques. Furthermore, the data is processed and analyzed using a simple statistical test. The results of the study show that the use of reading aloud methods can improve students' ability to read texts in grade III SDN. No. 028/XI Tanjung in 2017/2018 which can be seen from the increase in learning activities and improvement in learning outcomes. Student learning activities are getting better. The average score obtained by students also increased from 56.50 (pre-action) to 65.00 (cycle I) and 74.50 (cycle II). In addition, student learning completeness also increased from 33.33% (pre-action) to 60.00% (cycle I) and 86.67% (cycle II). Thus, the reading aloud method can be used as a method to improve students' ability to read texts.